Autologous implant of bone marrow mononuclear cells as treatment of induced equine tendinitis - Balesdent Barreira, Anna Paula [UNESP]; Alves, Ana Liz Garcia [UNESP]; Salto, Mere E. [UNESP]; Arnorint, Renee Laufer [UNESP]; Kohayagawa, Aguemi [UNESP]; Menarim, Bruno Carvalho [UNESP]; Mota, Ligia Sousa [UNESP] (Veterinary Solutions Llc, 2008)
Superficial digital flexor tendonitis is an important cause of lameness in horses and its incidence ranges from 13% to 30%, depending on the horse's activity. This injury can occur in yearlings and compromise its carriers by reinjury or even impossibility to return to athletic life. In spite of the long period required for tendon repair, the scar tissue presents lack of elasticity and stiffness. As current treatment strategies produce only marginal results, there has been great interest in research of therapies that influence the quality or the speed of tendon repair. Stem cell therapy has shown promising results in degenerative diseases and cases of deficient healing processes. This study aims to evaluate the influence of autologous mesenchymal bone marrow stem cells in tendon healing, comparing treated and non-treated tendons. Superficial digital flexor tendonitis lesions were induced by collagenase infiltration in both forelimbs of 6 horses, followed by autologous implant in one of the forelimbs of each animal. The horses were evaluated using clinical, ultrasonographic, histopathologic, and immunohistochemical parameters. Tendon biopsies were performed at Day 48. Results found in the treatment group, such as high inflammatory cells infiltration, extracellular matrix synthesis, reduced amount of necrosis areas, small increase in cellular proliferation (KI-67/MIB-1), and low immunoreactivity to transforming growth factor P I, suggested the acceleration of tendon repair in this group. Further studies should be conducted in order to verify the influence of this treatment on later phases of tendon repair. Overall, after analysis of the results, we can conclude that cellular therapy with the mononuclear fraction of bone marrow has accelerated tendon repair at 48 days after treatment.
Keywords: stem cell; mesenchymal cells; bone marrow; tendonitis; equine